The Influence of Electronic Word of Mouth on Purchasing Decisions with Attractive Streamers as a Moderating Variable: Penelitian - M. Anwar Aini; Rahmat Aji Nuryakin; Septi Wifasari; Udi Iswadi; Muhammad Aqshel Revinzky (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is a quantitative study with an explanatory approach that has the mission to create new hypotheses, modify hypotheses, and prove hypotheses by relying on previous studies. The data used in this study is secondary data obtained from various credible sources, such as books, scientific articles, magazines, and so on. The result in this article show that the Electronic Word of Mouth variable can have a positive relationship and a significant influence on Purchasing Decisions. This is because the P-Values in the table are positive and below the 0.05 significance level, namely 0.012. These results are in line with several previous studies, namely the research of (I Gusti et al. 2022); (Triwisnu Ronoprasetyo 2018) & (Alrwashdeh 2019). These results mean that better Electronic Word of Mouth by a company can increase the product's market share, increase public recognition, and ultimately increase the number of consumers who make purchasing decisions. In the next row, the Attractive Streamer variable can also moderate the influence of the Electronic Word of Mouth variable on Purchasing Decisions because the P-Values are positive and below the 0.05 significance level, namely 0.000.